Pengelolaan Sampah Untuk Produksi Magot Sebagai Bahan Baku Alternatif Untuk Ikan Air Tawar - Azis, Hasni Yulianti; Sukardi, Reski Wahyuni; Achmad, Marlina; Cangara, Arie Syahruni; Asnur, Andi Nurfadilah; Wahab, Fachrul; Saputra, Anugerah (Pakis Journal Institute, 2024)
Maggot (Black Soldier Fly/BSF larvae) is a high-protein resource that can be utilized as an alternative raw material for fish feed. Maggot production has great potential to reduce dependence on commercial feed while also utilizing organic waste. This community service program aims to introduce maggot production technology to fish farmers in Soppeng Regency, South Sulawesi, by using household organic waste as feed for snakehead fish (Channa striata). The activities include counseling on organic waste sorting, maggot cultivation training, and the application of maggot as fish feed. Through this program, the community gained an understanding of how to manage waste into high-quality maggot and use it as fish feed. The results showed that the community not only understood the maggot production process but also successfully utilized it independently to reduce fish feed costs. This program successfully raised awareness about the importance of organic waste management, supported freshwater fish farming, and had a positive impact on the environment. By utilizing maggot as an alternative feed, it is hoped that the community can develop more efficient and environmentally friendly fish farming, while also creating a sustainable organic waste management model.